ANALISIS PENGENDALIAN KUALITAS (QUALITYCONTROL) UNTUK MENINGKATKAN KUALITAS PRODUK YANG DIHASILKAN PADA CV BINA TEHNIK PEMATANGSIANTAR - Kiki, Erina; Lie, Darwin; Efendi, Efendi; Sisca, Sisca (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2019)
The purpose of this study are: 1. To find out the description of quality control and the products quality produced at CV Bina Tehnik Pematangsiantar. 2. To find out the implementation of quality control to improve the products quality produced at CV Bina Tehnik Pematangsiantar.The results of the study can be summarized as follows: 1. The process of quality control in the production process applied by CV Bina Tehnik Pematangsiantar is not optimal. 2. The aesthetic and conformance dimensions of the product quality produced by CV Bina Tehnik Pematangsiantar are not optimal. 3. From the results of the histogram, irregularities or discrepancies found at the end of the QC or inspection of the final product / finished product are dominated almost 80% by 2 (two) types of non-conformity, namely the state of paint / color and the function of lights and hoses. 4. From the analysis of fishbone diagrams, it is known that the causes of irregularities are derived from raw material, human or worker factors, work methods and the environment.Â Keyword: Brand Image, Service Quality and Customer Satisfaction